Sustainable Economic Development And Ecological Innovations - Uktam Jiyanov (Genius Journals, 2023)
The role of ecological innovations in sustainable economic development is considered in the article. In addition, the existing opportunities and problems in Uzbekistan in terms of economic development and ecological innovations were analyzed.
Keywords: Economic development; ecological innovations; market economy